Penanaman Nilai-Nilai Pendidikan Islam dan Life Skills dalam Kegiatan Market Day di SMPIT Al-Madani Kuantan Singingi - Utomo, Edi; Yeli, Salmaini; Mudasir, Mudasir (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
It is very important to continue to develop student potential, including by creating activities that combine the values of Islamic education and life skills. One of the interesting programs for students at SMPIT Al-Madani Kuantan Singingi is market day. This research aims to reveal how to instill Islamic education values and life skills in students during market day activities. This qualitative type of research uses interview techniques as a data collection instrument which is equipped with observation and documentation. The results of the research show that several aspects of Islamic education values, namely the values of divinity (tauhid), humanity (insaniyyah), unity (ittihad), deliberation (syuro), and justice ('is), in the domains of planning, implementation, and supervision can be implemented well. . However, the evaluation and follow-up domains have not been implemented enough. The second finding, namely the cultivation of life skills through market day activities, concluded that there were four aspects of life skills that were implemented well, namely the aspects of personal skills, rational thinking, social skills and vocational skills. However, one aspect of life skills, namely academic skills in the form of identifying variables, making connections, making hypotheses and conducting research, is not implanted or developed for students during market day activities. This is due to students' lack of intellectual abilities, as well as the short activity time which does not allow planning, implementation, reporting and evaluation of research.